Tartary buckwheat flavonoids ameliorate high fructose-induced insulin resistance and oxidative stress associated with the insulin signaling and Nrf2/HO-1 pathways in mice. Issue 8 (17th July 2017) - Hu, Yuanyuan; Hou, Zuoxu; Yi, Ruokun; Wang, Zhongming; Sun, Peng; Li, Guijie; Zhao, Xin; Wang, Qiang
Abstract : The present study was conducted to explore the effects of a purified tartary buckwheat flavonoid fraction (TBF) on insulin resistance and hepatic oxidative stress in mice fed high fructose in drinking water (20%) for 8 weeks. Abstract : The present study was conducted to explore the effects of a purified tartary buckwheat flavonoid fraction (TBF) on insulin resistance and hepatic oxidative stress in mice fed high fructose in drinking water (20%) for 8 weeks. The results indicated that continuous administration of TBF dose-dependently improved the insulin sensitivity and glucose intolerance in high fructose-fed mice. TBF treatment also reversed the reduced level of insulin action on the phosphorylation of insulin receptor substrate-1 (IRS-1), protein kinase B (Akt) and phosphatidylinositol 3-kinase (PI3K), as well as the translocation of glucose transporter type 4 (GLUT4) in the insulin-resistant liver. Furthermore, TBF was found to exert high antioxidant capacity as it acts as a shield against oxidative stress induced by high fructose by restoring the antioxidant status, and modulating nuclear factor E2 related factor 2 (Nrf2) translocation to the nucleus with subsequently up-regulated antioxidative enzyme protein expression. Histopathological examinations revealed that impaired pancreatic/hepatic tissues were effectively restored in high fructose-fed mice following TBF treatment. Our results show that TBF intake is effective in preventing the conversion of high fructose-induced insulin resistance and hepatic oxidative stress in mice by improving the insulin signaling molecules and the Nrf2 signal pathway in the liver.